The Effect of Fear of Missing Out (FoMO) on Intention to Use Strava: The Moderating Role of Social Media - Prasetyo Ari Herlambang; Edi Nurtjahjadi (International Journal of Management Science and Information Technology, 2026)
This study aims to analyze the effect of Fear of Missing Out (FoMO) on users’ intention to use the Strava application, with social media serving as a moderating variable. The increasing popularity of Strava, accompanied by the growing practice of sharing sports and fitness activities through social media platforms, suggests that users’ intention to use the application is influenced not only by health-related motivations but also by psychological and social factors. Individuals may be motivated to remain active and engaged within digital communities to avoid feeling excluded or left by their peers. A quantitative research approach was employed through a survey method involving 100 Strava users in Bandung City. Respondents were selected using purposive sampling techniques. The analysis of data was performed through basic linear regression and Moderated Regression Analysis (MRA) utilizing SPSS software. The results indicate that FoMO has a notably positive influence on the likelihood of utilizing the Strava application, as shown by a significance value of 0.001 (1.984). Additionally, social media was identified as a significant moderator in the connection between FoMO and the intention to use, evidenced by a significance value of 0.016 (< 0.05) and a positive interaction coefficient of 0.041. These findings suggest that increased levels of FoMO correlate with heightened intentions to engage with the Strava application and that social media enhances this connection. This research adds to the expanding literature on digital consumer habits, especially regarding the impact of psychological aspects on the use of fitness applications that are based on social media.